A Brachial Artery Pseudoaneurysm Treated with a Bifurcated Y-Shaped Artificial Vessel Graft - Oh, Joon seok; Eun, Seokchan (Archives of Plastic Surgery, 2022)
Brachial artery aneurysms are rare diseases that may be caused by infection or trauma. We report a case of a 71-year-old man who presented with a mass in his right antecubital fossa that increased in size slowly over time. Three years ago, the patient underwent ascending and total-arch replacement with artificial vessel graft to treat aortic root and ascending aorta aneurysm. Preoperative physical examination of right upper extremity showed a nonpulsatile mass with normal pulse of axillary, brachial, and radial arteries. The mass was removed and brachial artery reconstruction was done initially using saphenous vein graft. Two months later, the patient revisited with recurrent pseudoaneurysm, involving the bifurcation point of brachial artery. Aneurysm was totally resected and the brachial artery was reconstructed by interposition graft using a bifurcated GORE-TEX artificial vessel graft. The patient healed without complication and no recurrence was observed. Artificial vessel graft is an available option for reconstruction, and revascularization of vessel defect after excision of brachial artery aneurysm may involve bifurcation point.
Keywords: pseudoaneurysm; artificial vessel graft; brachial artery